Ulrich Beck's 'risk society' thesis and representations of food and eating in the British general interest women's magazine sector 1979-2003 - Wilkinson, Katherine Elizabeth (2006)
Beck asserts that since the 1950s, broad social transformations have radically altered collective relations. According to Beck, these changes have rendered conventional materialist analyses no longer appropriate to describe the new times we are living in. Beck links radical restructuring of organisational forms with the reorientation of cultural experience and modern selfhood as we move from ‘class’ to ‘risk’ positions (Beck, 1992: Beck and Beck-Gernsheim, 2003). This thesis employs a creative operationalisation of the key dimensions of Beck’s predictions, allowing them to be tested as hypotheses using data from the women’s magazine sector. Beck’s idea that cultural organisational practice is coming under increasing pressure to reorganise and encompass new principles of social orientation is critically evaluated.